Analisis Komparatif Kinerja Keuangan Perbankan Syariah dan Perbankan Konvensional - Aski, Farizal Julian; Suaryana, I Gusti Ngurah Agung (E-Jurnal Akuntansi; Vol 31 No 5 (2021), 2021)
The purpose of this study is to analyze: 1) Differences in the performance of Islamic banking and conventional banking. 2) How is the performance of Islamic banking and conventional banking. This research was conducted at banking companies registered with Bank Indonesia (BI) for a period of nine years, namely 2008-2016. The sampling technique used was purposive sampling technique. The number of samples obtained as many as companies with a total of 69 observations. Collecting data using non-participant observation methods. The analysis technique used is the comparative analysis Mann-Whitney test. The results of this study are: 1) Based on all the ratios that become proxies (CAR, NPL, OEOI, ROA, and LDR), there are significant differences in the performance of Islamic banking and conventional banking. 2) It turns out that during 2008-2016 the performance of Islamic banking was no better than conventional banking . Keywords: Syariah Banking; Conventional Banking; Comparative Analysis.